ENOLA HOLMES 2020 MOVIE: REVEALING GRAMMATICAL COHESION - Elik Khoirun Ni'mah; Afiifah Al Rosyiidah (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2021)
This study uses Enola Holmes movie script 2020 to reveal the types of grammatical cohesions. The theories used are the theory of Hasan and Halliday (1976). This study uses qualitative approach. The technique of data collection of this study is documentary. This study is analysed by using document as the data that are already transcribed. Based on the finding and data analysis, the writer finds 107 data of all the types of grammatical cohesion, they are: reference (81), substitution (3), ellipsis (12), and conjunction (11). The most dominant grammatical cohesion types used in the movie script is demonstrative reference “this” that occurs 17 times.AbstrakPenelitian ini menggunakan naskah film Enola Holmes 2020 untuk mengungkapkan jenis-jenis kohesi gramatikal. Teori yang digunakan adalah teori Hasan dan Halliday (1976). Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data penelitian ini adalah dokumentasi. Berdasarkan temuan dan analisis data, penulis menemukan 107 data dari semua jenis kohesi gramatikal, yaitu; referensi (81), substitusi (3), elipsis (12), dan konjungsi (11). Jenis kohesi gramatikal yang paling dominan digunakan dalam naskahfilm adalah referensi demonstratif “this” yang muncul sebanyak 17 kali.